Impact of social isolation during the COVID-19 pandemic on the mental health of university students and recommendations for the post-pandemic period: A systematic review - Tamiris Beppler Martins; Joaquim Henrique Lorenzetti Branco; Taís Beppler Martins; Gilmar Moraes Santos; Alexandro Andrade (Brain, Behavior, & Immunity - Health)
Introduction: Investigating the psychological impact caused by the interruption of social interactions on university students during the pandemic is essential, with a view to developing strategies to preserve mental health and academic performance. Objective: To analyze the impact of social isolation during the COVID-19 pandemic on the mental health of university students and propose recommendations for the post-pandemic period. Method: This systematic review was conduced in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and was registered in the International Prospective Register of Systematic Reviews (PROSPERO). Database searches were performed up to December 2024 in PubMed, EMBASE, Web of Science, Scopus, CINAHL, and PsycNET, using the terms “COVID-19,” “social isolation,” “mental health,” and “college students.” Studies were excluded if they focused on non-college populations, other causes of social isolation, physical health, or specific designs. Results: The initial search identified 3051 records and 68 studies were included in this review, with sample off 177,537 university students. Anxiety was the most commonly investigated variable (79.4%), followed by depression (75%) and stress (42.6%). Less frequently, studies highlighted the increase in alcohol and drug consumption and suicidal ideation. Some authors also investigated sleep quality, relating insomnia and emotional changes with the reduction in physical exercise. Anxiety symptoms related to online learning directly impacted academic performance. The assessment of the risk of bias showed that of the 68 studies included, 34 had a low risk of bias, 30 had a moderate risk of bias, and 4 had a high risk of bias. Conclusion: This study highlights the negative impact of the COVID-19 pandemic on the mental health of college students, particularly in relation to symptoms of anxiety, depression, and stress. Post-pandemic interventions should prioritize fostering healthy habits, such as ensuring quality sleep, engaging in moderate physical activity, and raising mental health awareness. Additionally, universities should implement proactive support systems to cultivate a safe and inclusive environment for students.